Retrieving Image from Noisy Version depending on Multiwavelet Soft-Thresholding with Smoothing Filter - Fahdel, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we describe a new method for image denoising. We analyze properties of the Multiwavelet coefficients of natural images. Also it suggests a method for computing the Multiwavelet transform using the 1st order approximation. This paper describes a simple and effective model for noise removal through suggesting a new technique for retrieving the image by allowing us to estimate it from the noisy image. The proposed algorithm depends on mixing both soft-thresholds with Mean filter and applying concurrently on noisy image by dividing into blocks of equal size (for concurrent processed to increase the performance of the enhancement process and to decease the time that is needed for implementation by applying the proposed algorithm on all four blocks concurrently) which are employed in order to remove the noise. The proposed method of image retrieving and smoothing outperforms the conventional methods that are used for image enhancement. The suggested algorithm and the evaluation test carried using Delphi V.5 package